The Future of Hybrid Narratology in «Alice Adventures in Wonderland» - Asunción LÓPEZ VARELA (1616, 2016)
In 2015 we have celebrated the anniversaries of the publication of Alice Adventures in Wonderland, one of the master works of World Literature, a work that shows a wish to unite knowledge from diverse disciplines in order to create a unified frame of understanding; a disposition known under the term «consilience», coined by William Whewell in 1840 and popularized by the Harvard Professor Edward O. Wilson in 1998. Carroll’s works, professedly for children, attest this interdisciplinary crossing between science and humanities. A semiotic study of these works may help clarify the foundations of analogic thought and its rupture. Alongside the exploration of the relationship between ambiguity and creativity, the essay seeks to enter the mechanisms that may enable intergeneric as well as intermedial translation of concepts and forms, each with its own specific languages. This would allow the study of Welt Literature, within Comparative Literature, from a formal perspective, and not just as a mechanism of circulation, as it has been studied until now.